LEARNING LOSSES IN MATHEMATICS IN THE POST PANDEMIC ERA - CALIMAG, NIKKA A. (Studies in Technology and Education, 2024)
This study seeks to add to the growing body of research that investigates the ways in which the COVID-19 pandemic has impacted the cognitive aspect of learning. This research aims to identify the learning losses of the fourth year Bachelor of Secondary Education (BSED) students majoring mathematics at the Isabela State University for the school year 2023-2024. This study utilized a diagnostic exam to quantitatively identify the specific competencies in algebra, geometry, statistics, and trigonometry that students are most struggling with. Results revealed evidential learning losses in the four learning areas. The insights gained from this study could help in designing teacher training programs, thereby equipping educators with the necessary skills to address the identified learning losses. Moreover, an in-depth and comprehensive review of the learning competencies where students have fallen behind provides baseline information for educators to develop strategies aimed at mitigating the learning losses and improving overall mathematical competence among students. It is recommended that targeted remediation and periodic teacher training be implemented to strengthen content knowledge and teaching strategies, ensuring students’ recovery and improved mathematical competence.